Towards the noise reduction of piezoelectrical-driven synthetic jet actuators - Jabbal, Mark; Jeyalingam, Jonne (Elsevier, 2017)
This work details an experimental investigation aimed at reducing the noise output of piezoelectrical-driven synthetic jet actuators while minimising peak jet velocity reduction. The study considers double-chamber actuator for anti-phase noise suppression and lobed orifice as a method to enhance jet turbulent mixing to suppress jet noise. The study involved the design, manufacture and bench test of interchangeable actuator hardware. Hot-wire anemometry and microphone recordings were employed to acquire velocity and sound pressure level measurements respectively across a range of excitation frequencies for a fixed diaphragm clamping and input voltage. The data analysis indicated a 26% noise reduction (16 dB) from operating a single-chamber, round orifice actuator to a double-chamber, lobed orifice one at the synthetic jet resonant frequency. Results also showed there was a small reduction in peak jet velocity of 7% (∼3 m/s) between these two cases based on orifices of the same discharge area. The electrical-to-fluidic power conversion efficiency of the double-chamber actuator was found to be 15% for both orifice types at the resonant frequency; approximately double the efficiency of a single-chamber actuator.